School Library – A Centre of Learning - Samantaray, Moorttimatee (THE PRIMARY TEACHER, 2006)
This article highlights the importance of education followed by the importance of books and libraries in self development. It also explores how books help children not only in teaching them a few facts but also in enriching their imagination, widening their outlook, developing a fact finding attitude and training them to use their leisure time properly. The social and educational significance of books for children cannot be underestimated. Realising the importance of school library in the educational process, NCF-2005 has emphasised its functioning as an essential component of the school at all levels.